Structure and Functional Properties of Proteins from Different Soybean Varieties as Affected by the 11S/7S Globulin Ratio - Yichen Hou; Lu Huang; Guangliang Xing; Xiaotian Yuan; Xiaoyan Zhang; Dongqing Dai; Xingxing Yuan; Xin Chen; Chenchen Xue (Foods)
Soybean (Glycine max (L.) Merrill) is a key source of plant protein, with 7S and 11S globulins being the primary fractions. This study investigated the protein content, protein composition, and 11S/7S globulin ratios of 411 soybean samples, and then selected six varieties (S1, S2, S3, S4, S5, and S6) for the analysis of the protein structures and functional properties. The results revealed that varieties with low 11S/7S ratios (S1, S2, and S3) exhibited relatively high random coil contents (20.11–22.94%) and lower β-sheet contents (34.17–38.37%), suggesting the presence of more loosely structured proteins. S2 showed good solubility (73.21%) and water-holding capacity (WHC) (2.73 g/g), which can improve product quality and yield. In contrast, varieties with high 11S/7S ratios (S4, S5, and S6) demonstrated more compact protein structures, increased surface hydrophobicity, larger particle sizes, lower absolute zeta potential values, and greater oil-holding capacity (OHC) values (7.58–8.48 g/g). S4, in particular, demonstrated superior emulsification properties, with emulsion activity index (EAI) (4.71 m2/g) and emulsion stability index (ESI) (58.73 min), which are widely used in the food industry such as in cake, ice cream, and bread. This study provides valuable information for the selection of soybean varieties with optimal 11S/7S ratios for processing soybean products.